SOSIALISASI PENERAPAN TEKNOLOGI OTOMATIS PENGERING â€œKERUPUK BAKARâ€ GUNA MENGATASI KETERGANTUNGAN PROSES PENGERINGAN DENGAN PANAS MATAHARI DI KELURAHAN JELMU KECAMATAN PELAYANGAN, KOTA JAMBI - Frastica Deswardani; Jesi Pebralia; Rista Mutia Anggraini; Muhhamad Ficky Afrianto; Lucky Zaehir Maulana (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The production of "kerupuk bakar" (grilled crackers) in Jelmu Subdistrict, Pelayangan District, Jambi City, faces drying challenges due to dependence on sunlight, particularly during the rainy season. This community service activity aims to introduce automatic drying technology to reduce weather dependency. The technology features a heating system with adjustable temperature and time settings, providing an efficient, fast, and consistent drying process. Methods include training on equipment usage and mentoring for local "kerupuk bakar" entrepreneurs. Results show that the implementation of automatic drying technology improves productivity, quality stability, and local entrepreneurs' income. This activity is expected to be a long-term solution to support economic growth in the regionâ€™s home industries.